Reduction in Cortisol Inactivation is Part of the Adrenal Stress Response to Cardiac and Noncardiac Pediatric Surgery: A Prospective Study Using Gas Chromatography-Mass Spectrometry Analysis - Heckmann, M.; d’Uscio, C. H.; Steckel, H.; Neuhaeuser, C.; Bödeker, R.-H.; Thul, J.; Schranz, D.; Frey, B. M. (Hormone and Metabolic Research, 2014)
We examined the hypothesis that major cardiac surgery triggers a more intense adrenal stress response than less intensive noncardiac surgery, which then alters cortisol inactivation. Urinary excretion rates of glucocorticoid metabolites were determined before and after surgery using gas chromatography-mass spectrometry in 29 children undergoing scheduled major cardiac surgery and 17 control children undergoing conventional noncardiac surgery in a prospective observational study. Excretion rates of glucocorticoid metabolites were summed and corrected for creatinine excretion to calculate cortisol production rates (mg/mmol creatinine/m2 body surface area). Precursor/product ratios from individual metabolites were calculated to characterize cortisol inactivation (11β-hydroxysteroid dehydrogenase). Postoperatively, median cortisol production rates increased in both groups (MCS: from 2.7 to 9.3; controls: from 2.7 to 5.8; p<0.001) with no significant difference between groups (p=0.12). Ratios of cortisol to cortisone metabolites, indicating the overall activity of 11β-hydroxysteroid dehydrogenase, increased postoperatively in both groups (p<0.001). In conclusion, surgery resulted in a distinct postoperative increase in cortisol production. In contrast to our hypothesis, children undergoing major cardiac surgery did not show an increased adrenal stress response compared to children undergoing conventional surgery. Furthermore, the reduction in cortisol inactivation appears to be an essential part of the stress response to pediatric surgery in general.
Keywords: 11β-hydroxysteroid dehydrogenase; glucocorticoid; precursor/product ratio